Collateral Damage: A Narrative Review on Epidemics of Substance Use Disorders and Their Relationships to Sexually Transmitted Infections in the United States. Issue 7 (14th July 2021) - Strathdee, Steffanie Ann; Bristow, Claire C.; Gaines, Tommi; Shoptaw, Steven
Abstract : This narrative review describes the relationship between the US opioid epidemic, its relationship to the epidemiology of sexually transmitted infections, and opportunities for integrated interventions. Abstract: Associations between substance use disorders and outbreaks of HIV and acute viral hepatitis have received considerable attention, but less research has focused on links between substance use disorders and sexually transmitted infections, apart from alcohol misuse. This narrative review describes the history of this public health crisis in the United States and direct and indirect effects opioids and specific stimulants have on high-risk sexual behaviors. We also review the epidemiology of sexually transmitted infections associated with opioids and stimulants in the United States and discuss opportunities for integrated interventions.